Athlete leadership in sport teams: Current understanding and future directions - Cotterill, S. T.; Fransen, K. (International Review of Sport and Exercise Psychology, 2016)
Leadership is a fundamental aspect of sports performance, particularly within team sport environments. Over the past 25 years there has been significant research exploring the role of the coach/manager in this regard. However, this only represents one aspect of leadership within the sporting domain. Equally important, although far less examined, is the concept of athlete leadership. The role of athlete leaders, both formal (e.g., the captain) and informal (such as motivators and cultural architects) can have a significant impact upon a range of team-related factors including satisfaction, cohesion, and team dynamics. However, the mechanisms through which this impact occurs are less well understood. Also, while the development of leadership skills has been proposed as an important aspect of coach development programmes there is very little consensus regarding the approaches that should be adopted in developing athlete leaders and their associated leadership skills. This paper reviews the existing literature relating to athlete leadership seeking to provide clarity regarding current understanding. Building upon this base the paper then highlights future areas for research and theoretical development.